Analysis of Electric Voltage Signals Produced by Plants Using Matlab - Pratama, Destra Andika; Hasan, Yordan; Rini, Ajeng Setyo (TEPIAN, 2023)
Some plant species can move rapidly in response to various stimuli (e.g. touch). Some of these plant species are Mimosa Pudica L (Putri Ashamed) and the Venus Fly Trap plant. Previous electrophysiological studies have shown that electrical signals travel long distances and quickly through the Mimosa pudica plant (Putri Malu). Thigmotactic or seismonastic movements in Mimosa pudica, such as responses to touch, Mimosa pudica are electrically and mechanically analyzed using matlab software, i.e. if the voltage of the electric signal the output is 506mV-800mV or higher. Venus Fly Trap plant in response to mechanical stimulation. Electrical signaling and rapid closing of the Venus flytrap plant that electrically stimulated between the sheath and lobe closes the Venus flytrap leaf by activating a mechanically stimulated motor call from the trigger hair. Biologically closed electrical circuits operating over long distances in biological networks are electrically and mechanically analyzed using matlab software i.e. the generated electrical voltage signal is 512mV-555mV or higher. Activation of such a circuit can cause various physiological and biophysical responses. Here, we analyze the biologically open and closed electrical circuits of sensitive plants Venus’s fly trap and shy daughter by data acquisition with the measurements taken on this assay taking a time duration of approximately 9 s per test.